Analisis Kriminologi Terhadap Kasus Penipuan Online K-Pop Merchandise di Group Order X Melalui Platform Line - Sofia Salsabila Ananda; Triny Srihadiati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze online fraud crimes in the group order (GO) system that occurs among K-Pop fans, focusing on how perpetrators build consumer trust and take advantage of opportunities in the online transaction system. Through a qualitative approach and case studies, this study found that perpetrators intentionally create trust in consumers through friendly and responsive communication. This case is often found in the K-pop fan community, where perpetrators, who are generally still in school, build trust through open promotions on social media and relaxed and responsive communication. Over time, perpetrators begin to reduce interaction and lack transparency until they finally disappear after the funds are collected. These findings are analyzed using routine activity theory, which emphasizes that crime occurs because perpetrators are motivated by appropriate consumers without supervision that can prevent crime. In this context, a weak pre-order system, lack of consumer education, and limited supervision from the authorities play a role as driving factors for crime.